Communicating carbon removal - Bellamy, Rob; Raimi, Kaitlin T. (Frontiers in Climate, 2023)
Removing carbon dioxide from the atmosphere is "unavoidable" if net zero emissions are to be achieved, and is fast rising up the climate policy agenda. Research, development, demonstration, and deployment of various methods has begun, but technical advances alone will not guarantee a role for them in tackling climate change. For those engrossed in carbon removal debates, it is easy to forget that most people have never heard of these strategies. Public perception of carbon removal is therefore particularly sensitive to framings -the ways in which scientists, entrepreneurs, activists, politicians, the media, and others choose to organize and communicate it. In this perspective, we highlight four aspects of carbon removal for which their framing will play a decisive role in whether -and how -different methods are taken forward. First, the use of analogies can be helpful in guiding mental models, but can also inadvertently imply processes or outcomes that do not apply in the new example. Second, a taxonomic split between 'nature-based' and 'technological' methods threatens to divert attention from the actual qualities of different methods and constrain our policy options. Third, people are likely to overestimate the emissions-reduction potential of carbon removal, but this misperception can be corrected. Fourth, communications overlook the social arrangements for carbon removal and the alternative trajectories that implementation may take. We end by offering key recommendations for how we can communicate carbon removal more responsibly.